Perjalanan Seni dan Budaya: Jejak Karya-Karya Raden Saleh dalam Perspektif Historis - Yandi Syaputra Hasibuan (Local History & Heritage, 2023)
Raden Saleh, a prominent Indonesian artist, has regained attention in recent times with the release of the film "Mencuri Raden Saleh" (Stealing Raden Saleh). One of the film scenes depicts a painting portraying the capture of Prince Diponegoro, which is said to represent resistance against the Dutch colonial rule and nationalism. This raises the need to delve into Raden Saleh's life, the emergence of the painting depicting the capture of Prince Diponegoro, and to understand the historical context and Raden Saleh's position within it. It is essential to provide a clear historical framework to avoid any misconceptions about Raden Saleh and his role. This research utilizes the Historical Method, beginning with the identification of the topic. The heuristic phase involves gathering primary sources such as newspapers, articles, magazines, and online archives like Delpher.nl and the Library University Leiden KITLV. Secondary sources such as books and journals are also employed. The collected sources undergo verification through external criticism to ensure their authenticity and internal criticism to establish the credibility of historical facts. Subsequently, the verified findings are interpreted through analysis and synthesis to construct a historical narrative. Finally, historiography is employed to reconstruct the gathered historical facts.